HIF-1α transgenic bone marrow cells can promote tissue repair in cases of corticosteroid-induced osteonecrosis of the femoral head in rabbits. - Hao Ding (Public Library of Science (PLoS), 2013)
Although corticosteroid-induced osteonecrosis of the femoral head (ONFH) is common, the treatment for it remains limited and largely ineffective. We examined whether implantation of hypoxia inducible factor-1α (HIF-1α) transgenic bone marrow cells (BMCs) can promote the repair of the necrotic area of corticosteroid-induced ONFH. In this study, we confirmed that HIF-1α gene transfection could enhance mRNA expression of osteogenic genes in BMCs in vitro. Alkaline phosphatase activity assay and alizarin red-S staining indicated HIF-1α transgenic BMCs had enhanced osteogenic differentiation capacity in vitro. Furthermore, enzyme linked immunosorbent assay (ELISA) for VEGF revealed HIF-1α transgenic BMCs secreted more VEGF as compared to normal BMCs. An experimental rabbit model of early-stage corticosteroid-induced ONFH was established and used for an evaluation of cytotherapy. Transplantation of HIF-1α transgenic BMCs dramatically improved the bone regeneration of the necrotic area of the femoral head. The number and volume of blood vessel were significantly increased in the necrotic area of the femoral head compared to the control groups. These results support HIF-1α transgenic BMCs have enhanced osteogenic and angiogenic activity in vitro and in vivo. Transplantation of HIF-1α transgenic BMCs can potentially promote the repair of the necrotic area of corticosteroid-induced ONFH.